Do mutual fund managers' possess style liquidity timing abilities?. Issue 3 (10th November 2020) - Alam, Mahfooz; Ansari, Valeed Ahmad
Abstract : Purpose: This paper investigates the style timing and liquidity style timing vis-à-vis the market, size, value and momentum factors of the actively managed Indian equity mutual funds. Design/methodology/approach: We examine the style timing of the funds using the augmented Carhart four-factor model by incorporating timing measures (Treynor and Mazuy; Henriksson and Merton). Based on this, the study explores the four-factor liquidity and volatility style timing exhibited by fund managers. The sample is from April 2000 to March 2018 and spans the volatile 2008 subprime economic crises. The sample comprised 182 actively managed equity funds from various sizes and was considered to be a well-diversified sample. Findings: The results of our study provide strong evidence of market liquidity timing in India. No other style timing skills are observed in our analysis. Our results also imply that the fund managers might misidentify size timing as market timing if integrated liquidity timing measures are not employed, leading to false conclusions. Research limitations/implications: The findings of our study imply that the fund managers might misidentify size timing as market timing if integrated liquidity timing measures are not employed, leading to false conclusions. Originality/value: This study, to our knowledge, is the first attempt to investigate the portfolio-based style timing in the Indian context.